Strategi Pembelajaran Bahasa Indonesia Berdasarkan Pendekatan Komunikatif - Khaerudin Kurniawan (Universitas Negeri Malang, 2016)
This study aims at improving the teacher's capability in arranging and implementing the strategy of learning Bahasa Indonesia at SLTP 8 Yogyakarta. The research was conducted at class I.3 from July to November 2000 in three cycles. Based on the analysis, it could be concluded that the teacher's comprehension about the communicative approach increased. It was also found in arranging the lesson plan. It was proved by the increase of student's score, activity, and motivation in learning process. The average score on listening was 0.85, speaking was 1.16, reading was 0.4, and writing was 0.78